Associations between branched chain amino acid intake and biomarkers of adiposity and cardiometabolic health independent of genetic factors: A twin study. (15th November 2016) - Jennings, Amy; MacGregor, Alex; Pallister, Tess; Spector, Tim; Cassidy, Aedín
Abstract: Background: Conflicting data exist on the impact of dietary and circulating levels of branched chain amino acids (BCAA) on cardiometabolic health and it is unclear to what extent these relations are mediated by genetics. Methods: In a cross-sectional study of 1997 female twins we examined associations between BCAA intake, measured using food frequency-questionnaires, and a range of markers of cardiometabolic health, including DXA-measured body fat, blood pressure, HOMA-IR, high-sensitivity C-reactive protein (hs-CRP) and lipids. We also measured plasma concentrations of BCAA and known metabolites of amino acid metabolism using untargeted mass spectrometry. Using a within-twin design, multivariable analyses were used to compare the associations between BCAA intake and endpoints of cardiometabolic health, independently of genetic confounding. Results: Higher BCAA intake was significantly associated with lower HOMA-IR (− 0.1, P -trend 0.02), insulin (− 0.5 μU/mL, P -trend 0.03), hs-CRP − 0.3 mg/L, P -trend 0.01), systolic blood pressure (− 2.3 mmHg, P -trend 0.01) and waist-to-height ratio (− 0.01, P -trend 0.04), comparing extreme quintiles of intake. These associations persisted in within-pair analysis for monozygotic twins for insulin resistance ( P  < 0.01), inflammation ( P  = 0.03), and blood pressure ( P  = 0.04) suggesting independence from genetic confounding. There was no association between BCAA intake and plasma concentrations, although two metabolites previously associated with obesity were inversely associated with BCAA intake (alpha-hydroxyisovalerate and trans-4-hydroxyproline). Conclusions: Higher intakes of BCAA were associated, independently of genetics, with lower insulin resistance, inflammation, blood pressure and adiposity-related metabolites. The BCAA intake associated with our findings is easily achievable in the habitual diet.